2019
DOI: 10.1002/pbc.27774
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of primary care physicians in care for childhood cancer survivors

Abstract: Background Childhood cancer survivors (CCS) are at risk of developing long‐term morbidity, which is likely to be presented to a primary care physician (PCP). Therefore, insight into CCS's PCP‐based health care use is needed. We investigated the volume and underlying health problems of PCP‐based health care use and the determinants for PCP‐based health care use in CCS. Procedure Data from a Dutch cohort of 6018 eligible five‐year CCS were linked to the Nivel Primary Care database, which contains detailed data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Additionally, some CNS tumor survivors had visits due to endocrine and nervous system disorders. Our findings are in line with previous studies that also found a higher risk of outpatient visits [12,13] due to secondary malignancy (neoplasms), endocrine, and neurological conditions [13] among CCS than among references without such medical history.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, some CNS tumor survivors had visits due to endocrine and nervous system disorders. Our findings are in line with previous studies that also found a higher risk of outpatient visits [12,13] due to secondary malignancy (neoplasms), endocrine, and neurological conditions [13] among CCS than among references without such medical history.…”
Section: Discussionsupporting
confidence: 93%
“…However, childhood cancer survivors (CCS) are at higher risk of chronic health conditions compared to individuals without childhood cancer [2][3][4][5][6]. Studies have shown an overall higher risk of hospitalization [7][8][9][10][11][12], outpatient visits [12,13], and prevalence of chronic health conditions (all grades) (as high as 77% of all CCS with an average of 3-4 diagnoses/CCS [2,14]) among CCS compared to among references without childhood cancers. Although the prevalence of chronic health conditions, hospitalization, and outpatient visits is higher among young adult CCS than references, their burden in terms of affected work capacity might vary largely.…”
Section: Introductionmentioning
confidence: 99%
“…Survivors can be divided into risk groups and suggestions can be made on their optimal individual care according to available guidelines 31 . However, scarce knowledge and experience of adult specialists on childhood cancer survivorship limit the availability of appropriate services 33,34 . Establishing optimal long-term survivor care is vital to prevent late morbidity and mortality to further improve outcome of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Until present, 35 published reports from national and international collaborative studies include data from the LATER 1 study, 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 addressing cardiac outcomes, 20 , 21 , 22 , 23 subsequent tumors, 6 , 14 , 15 , 19 , 24 , 25 , 26 , 29 , 33 , 34 , 35 , 42 , 44 , 45 burden of disease, 31 , 32 mort...…”
Section: Resultsmentioning
confidence: 99%